INSTAGRAM SEBAGAI MEDIA INFORMASI DAN PROMOSI MINEWS.ID - Ernawati, Erna (JURNAL SAHID DA'WATII, 2024)
The aim of this study was to analyze how Minews.id, an online media portal, utilized Instagram as an information and promotion medium. This study used a qualitative approach by using data collection techniques through observation, interview, and literature review. The result showed that Instagram, as a popular social media platform, was not only used by individuals but also by several companies as a tool to share information related to their products or services with persuasive messages and attract the curiosity and interest of the public.